Anuran communities in the dry karst ecosystem of Central Java, Indonesia - MARIO FEBRIYONO; IKE NURJUITA NAYASILANA; GALUH MASYITHOH (Society for Indonesian Biodiversity, 2023)
Abstract. Febriyono M, Nayasilana IN, Masyithoh G. 2023. Anuran communities in the dry karst ecosystem of Central Java, Indonesia. Biodiversitas 24: 6484-6492. Dry physical conditions characterize karst ecosystems. This affects the distribution of the Anura-amphibian that depend on water sources. The presence of anurans in an ecosystem can be used as an environmental bioindicator. In this study, we used a visual encounter survey to document and provide information on the presence of anurans in Pucung village, Wonogiri District, Central Java, Indonesia, to provide information for the sustainable management of this karst ecosystem. The study was conducted from January to March 2023. Observations were made at two sites–Gundi Hamlet and Dunggudel Hamlet–and covered each of the different land covers found in the region. Then, anuran species diversity was analyzed using an index calculated using Barbour diversity analysis and the Shannon-Wiener diversity index (H'), species richness index, species dominance index, and species evenness index. Environmental parameters were investigated using canonical correspondence analysis. We found eight species belonging to five families. The Rice Field Frog (Fejervarya cancrivora) was the most abundant species, with 95 individuals. The least common species was Asian Toad (Duttaphrynus melanostictus) with two individuals. The H' values ranged from 1.21 to 1.58. The highest diversity value was found in the community forest habitat. A comparison of the values for the environmental factors, including climate (air temperature and humidity) and water pH in the three habitat types studied, showed low significance, meaning that the three habitat types were suitable for the presence of anurans. Based on the observations and environmental factors, we determined that the karst ecosystem in Pucung village could support a diversity of anuran species.